Proceedings of the 2002 ACM Symposium on Applied Computing 2002
DOI: 10.1145/508791.508914
|View full text |Cite
|
Sign up to set email alerts
|

Mobile delivery of news using hierarchical query-biased summaries

Abstract: This paper presents the results of a study aimed at measuring the usefulness of presenting the results of an Information B~trieval search on WAP mobile phones. The experimentation focuses on presenting automatically-generated summaries of newspaper articles of increasing length on a mobile phone interface and in studying the differences in users' perception of relevance of the retrieved documents. The aim is to study experimentally how users' perception of relevance varies depending on the length of the summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…Questionnaires completed by the users suggest that hierarchical query-biased summaries are useful and assist users in making relevance judgments. The results are consistent with the findings of our previous study that found for small screen displays (WAP mobile phone interface) users showed both a preference and better performance with the shorter summary lengths (7% of the document length) [20]. Further support for presenting concise relatively brief summaries on small screen devices comes from the findings of a recent WAP usability study 7 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Questionnaires completed by the users suggest that hierarchical query-biased summaries are useful and assist users in making relevance judgments. The results are consistent with the findings of our previous study that found for small screen displays (WAP mobile phone interface) users showed both a preference and better performance with the shorter summary lengths (7% of the document length) [20]. Further support for presenting concise relatively brief summaries on small screen devices comes from the findings of a recent WAP usability study 7 .…”
Section: Discussionsupporting
confidence: 91%
“…phone interface [20]. In particular, the average levels of precision are similar to those found when documents summaries are presented to a user on a computer screen [22] but have slightly lower levels of recall.…”
Section: Experimental Measuressupporting
confidence: 60%
See 3 more Smart Citations